Ho‐Mediated Alkyne Reactions at Low Temperatures on Ag(111). Issue 60 (4th October 2018) - Hellwig, Raphael; Uphoff, Martin; Paintner, Tobias; Björk, Jonas; Ruben, Mario; Klappenberger, Florian; Barth, Johannes V.
Abstract: Low‐temperature approaches to catalytic conversions promise efficiency, selectivity, and sustainable processes. Control over certain coupling reactions can be obtained via the pre‐positioning of reactive moieties by self‐assembly. However, in the striving field of on‐surface synthesis atomistic precision and control remains largely elusive, because the employed coupling reactions proceed at temperatures beyond the thermal stability of the supramolecular templates. Here, utilizing scanning tunneling microscopy, we demonstrate terminal alkyne on‐surface reactions mediated by Ho atoms at a weakly reactive Ag(111) substrate at low‐temperatures. Density functional theory calculations confirm the catalytic activity of the involved adatoms. Pre‐deposited Ho induces alkyne dehydrogenation starting at substrate temperatures as low as 100 K. Ho arriving at molecularly pre‐covered surfaces held at 130 and 200 K produces covalent enyne‐linked dimers and initiates cyclotrimerization, respectively. Statistical product analysis indicates a two‐step pathway for the latter, whereby the enyne intermediates influence the distribution of the products. High chemoselectivity results from the absence of cyclotetramerization and diyne‐forming homocoupling. Our analysis indicates that mainly the arriving Ho adatoms enable the coupling. These findings support the concept of dynamic heterogeneity by single‐atom catalysts and pave the way for alternative means to control on‐surface reactions. Abstract : Ho‐mediated on‐surface reactions : Deposition of Ho atoms onto the weakly reactive Ag(111) surface triggers low‐temperature Ho‐catalyzed terminal alkyne dehydrogenation (≈100 K, not shown), enyne formation (130 K, left), and cyclotrimerization (200 K, right) supporting the concept of dynamic heterogeneity.